A Randomized, Double‐Blind, Placebo‐Controlled, Multiple Dose Escalation Study to Evaluate the Safety and Pharmacokinetics of ELX‐02 in Healthy Subjects. Issue 8 (19th January 2021) - Leubitz, Andi; Vanhoutte, Frederic; Hu, Ming‐yi; Porter, Kaela; Gordon, Efrat; Tencer, Kathleen; Campbell, Kathleen; Banks, Kate; Haverty, Tom
Abstract: ELX‐02 is an investigational compound being developed as a therapy for genetic diseases caused by nonsense mutations such as cystic fibrosis. Structurally, ELX‐02 is an aminoglycoside analogue that induces read‐through of nonsense mutations through interaction with the ribosome, resulting in the production of full‐length functional proteins. This phase 1 multiple‐ascending‐dose trial evaluated the safety and pharmacokinetics of ELX‐02 in 62 healthy volunteers. ELX‐02 plasma exposure was dose proportional, with no apparent accumulation, and followed by renal elimination. The most reported adverse event was injection site reactions that were mild to moderate in severity. At the top dose of 5.0 mg/kg, 1 of 6 subjects experienced auditory threshold changes in which ototoxicity could not be clearly ruled out, and 2 of 6 had hearing threshold changes consistent with possible ototoxicity. Two of 3 subjects receiving placebo in the 5.0 mg/kg group also had significant hearing threshold changes. All observed hearing threshold changes resolved or were trending toward resolution after withdrawal of the study drug. No severe or serious adverse events were reported.The results of this study support the evaluation of ELX‐02 in phase 2 clinical trials with patients that have genetic diseases caused by nonsense mutations.